The Formulation, Characterization, and Antibacterial Activity of Solid Soap Containing Guava Leaf Extract (Psidium guajava L.) and Precipitated Calcium Carbonate - Sri Handayani; Hendri Faisal; Shaflina Izar; Togito Febrina Sitorus (Jurnal Kesmas Prima Indonesia, 2026)
Bath soap is defined as a sodium compound with fatty acids used as a body cleanser, which generates foam and does not cause skin irritation. Beyond cleansing the skin from external dirt, soap can also function to eliminate bacterial skin infections. Prior investigations have verified that the saponins, tannins, and flavonoids concentrated in guava leaves exhibit robust antibacterial activity. The objective of this study was to determine the physicochemical properties of a solid soap formula containing the ethanol extract of guava leaf and precipitated calcium carbonate, including texture, color, pH, moisture content, hardness, and other relevant properties. This study employed a laboratory experimental research method. The procedure involved the preparation of guava leaf (Psidium guajava L.) simplicia, followed by extraction with a 70% ethanol solvent via maceration. Subsequently, the solid soap formulation was created using the guava leaf extract and precipitated calcium carbonate, followed by evaluation and antibacterial activity testing against Staphylococcus aureus bacteria. The pH evaluation test yielded an average value of 9.09 for the blank formula, while the average pH values for the active formulas were 9.13 for FI, 9.30 for FII, 9.23 for FIII, and 9.12 for the positive control (comparator). Based on the antibacterial testing results, the solid soap containing guava leaf ethanol extract demonstrated strong antibacterial activity against Staphylococcus aureus. The inhibition zone diameters were recorded as 0 mm for F0 (blank), 11.6 mm for FI (10% concentration), 10.9 mm for FII (15% concentration), 11 mm for FIII (20% concentration), and 11.3 mm for K+ (comparator). The research indicates that the ethanol extract of guava leaves combined with precipitated calcium carbonate (PCC) can be successfully formulated into a stable solid soap that meets the physical quality standard requirements according to the Indonesian National Standard (SNI).